Estimation of surface film conductance during cooling of fish packages - Sapuan, S. M.; Abbas, K. A.; Ansari, F. A. (Sage Publishing, 2005)
The present paper deals with the findings of an ongoing research project regarding quality measurements in cold preserved freshwater fish. An empirical correlation, reported elsewhere, was used to design experiment for prediction of surface film conductance through transient temperature-time measurements in the fish flesh during its cooling in a chilled air duct at a constant temperature of 1 &DEG; C. This surface film conductance was then used for numerical calculations of temperature variations on the basis of the finite difference method. Calculations were repeated with surface film conductance values from the Nu-Re relation most prevalently used. The two results were compared graphically at many locations inside the tested fish samples to establish that the present approach gives much improved results compared with the existing schemes available in the literature.